Satellite-Observed Monthly Variability of Sea Surface Chlorophyll-a Concentration: A Case Study in East Malaysia - Kemarau, Ricky Anak; Eboy, Oliver Valentine; Sakawi, Zaini; Suab, Stanley Anak; Noor, Noorashikin Md (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Monsoon variability plays a pivotal role in Malaysia's economy, yet research has overlooked its impact on chlorophyll-a distribution in the South China Sea. Our study addresses this gap, focusing on the monsoon's influence on chlorophyll-a levels in Malaysian waters, enhancing the understanding of regional marine ecosystems and their economic significance. The objective of this research is to examine the Northeast Monsoon (NEM) and Southwest Monsoon (SWM) influence on the variability of chlorophyll-a concentration distribution and its relation to the total number of fish landings in East Malaysia in the year 2019. To achieve this goal, MODIS data was utilized. Literature reviews have indicated that remote sensing wavelength reflectances at 443 and 555 nanometers were also employed to assess phytoplankton biomass and suspended sediment concentrations. An increase in the phytoplankton absorption coefficient at 443 nanometers, coupled with a higher backscattering constant for dissolved and detrital material, correlates with elevated phytoplankton biomass and suspended sediment concentrations. The investigation revealed significant variability in chlorophyll-a concentrations across monsoon seasons, with values peaking at 36.5 mg mˉ³ during the SWM, which contrasts markedly with the NEM. This influence of suspended sediment and organic matter may introduce bias to chlorophyll-a concentration measurement. Accordingly, an increase in the phytoplankton absorption constant at 443 nanometers, coupled with a higher backscattering coefficient for dissolved and detrital material, correlates with elevated phytoplankton biomass and suspended sediment concentrations. The investigation revealed significant variability in chlorophyll-a concentrations across monsoon seasons, with values peaking at 36.5 mg mˉ³ during the SWM, which contrasts markedly with the NEM. This variability underscores the profound impact of monsoon dynamics on chlorophyll-a distribution in East Malaysia, influencing both marine biomass and fishery yields. These findings suggest that different monsoon seasons lead to varying total fish landings in East Malaysia. Established on the observed differences in chlorophyll-a dispersion, remote sensing technology explains higher fish catches during the SWM than the NEM. This information is vital for fishers, as it aids in optimizing their operation and reducing overall costs.